شعرية المكان ومفارقة الزمن في القصة الجزائرية "قصة مدينة الأنوار" لعبد الحكيم أوكفيل ـ نموذجا - آماني داودي; عائشة غدير إبراهيم; وداد زكور فرحات; فاطمة الزهراء سويد (جامعة الوادي - University of Eloued, 2025)
الملخص: تناولنا في هذه المذكرة دراسة لعنصري الزمان والمكان في القصة الجزائرية التي تظمنت فصلين، حيث تناول الفصل الاول ادب القصة واهمية مكون الحيز والذي يعد من اهم المكونات السردية التي تبنى عليها القصة القصيرة، بينما تناول الفصل الثاني جمالية المكان والزمان في قصة مدينة الانوار حيث طبقنا المعطيات النظرية لعنصري الزمان والمكان، كما حمل كل فصل مجموعة مباحث ومطالب نظمت عناصر المذكرة، كما توصلنا في الاخير لمجموعة نتائج لهذا البحث منها: تنوع القصة بين الطويلة والقصيرة. غالبا ماتحمل القصص حكما. كما تستخدم القصة لغة رمزية وبسيطة. Abstract: In this memorandum, we study the elements of time and place in Algerian fiction, which includes two chapters. The first chapter deals with the literature of fiction and the importance of the spatial component.Which is considered one of the most important narrative components on which the short story is built, while the second chapter dealt with the aesthetics of place and time in the story of the City of Lights, where we applied the theoretical data of the elements of time and place.Each chapter also included a set of topics and demands that organized the elements of the memorandum, and from this we arrived at a set of results for this research, including:The stories vary between long and short. They often contain morals. They also use simple, symbolic language.
دراسات أدبية
Keywords: الزمكان _ الحيز _ جمالية_ الزمكانية شعرية _ القصة_ مدينة الانوار _ مناهج التحليل _ مظاهر _تقنيات; Spacetime _ Space _ Aesthetics _ Spatiotemporal Poetics _ Story _ City of Lights _ Analytical Methods _ Aspects _ Techniques.